VALOR DE LA IONTOFORESIS CON SALICILATO DE SODIO EN EL REUMATISMO CARDIOVASCULAR - GUERRA PEREZ CARRAL, FRANCISCO; CHAVEZ, N (Instituto Politécnico Nacional, Escuela Nacional Ciencias Biología, Laboratorio Bioquimica, CD MEXICO, DF, MEX, 1947)
The effects of local heating or cooling of the regions of cardiac ventricles in contact with recording electrodes were studied in dogs, cats, turtles and frogs The responses were recorded through unpolarizable leads and a direct-coupled amplifier by mean
ARCH INST CARDIOL MEX
Keywords: VALOR, IONTOFORESIS, SALICILATO, SODIO, REUMATISMO, CARDIOVASCULAR; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA